(untitled) (Latakia University Journal -Engineering Sciences Series, 2016)
إن من وظائف نظام التعليق في السيارة عزل الاهتزازات الناتجة بسبب وعورة الطريق عن السائق وتأمين قيادة مريحة. ولكن تصميم أنظمة التحكم لأنظمة التعليق نصف الفعالة أمر صعب بسبب اللاخطية التي تبديها العناصر المكونة لهذه الأنظمة مما جعل الدراسات المرتبطة بها تتسم بالتعقيد. لذلك وفي سبيل تحسين أداء أنظمة التعليق نصف الفعالة دون تكلف عناء تصميم متحكم يعتمد على النموذج مباشرة تم تصميم نظام تحكم باستخدام المتحكم الضبابي ذاتي التنظيم بالاعتماد على مبدأ التأخير في الجزاء للتحكم بنظام تعليق نصف فعال يستخدم المخمدات المغناطيسية الريولوجية. إذ يقوم المتحكم بمحاولة تحسين أداء النظام بناء على الاستجابة المرغوبة الموصوفة في جدول الجزاء. يستخدم المتحكم الضبابي متغيرين كدخل للمتحكم وهما سرعة الكتلة المعلقة وسرعة الكتلة غير المعلقة. باستخدام نموذج ربع سيارة بدرجتي حرية تمت نمذجة ومحاكاة النظام في بيئة MATLAB & Simulink®، وتمت مقارنة النتائج مع استراتيجية sky-hookالواسعة الاستخدام، حيث أظهرت المحاكاة قدرة المتحكم الضبابي ذاتي التنظيم على تقديم نتائج جيدةفي التقليل من تسارع الكتلة المعلقة في نماذج الطرق المتنوعة بالمقارنة مع استراتيجية sky-hook. One ofa car’s suspension system functions is to isolate vibrations resulting from road on the driver and ensure a comfortable ride. But the design of control systems for semi-active suspension systems is difficult because of the non-linearity of the constituent elements of these systems which make the researches related to it characterized by complexity. So in order to improve the performance of semi-active suspension systems without bearing the effort of designing a model based controller, a control system is designed using self-organizing fuzzy controller based on the principle of delay-in-penalty to control a semi-active suspension system which uses a magneto rheological damper. The controller tries to enhance system performance using the desired response as it is described in the penalty table. The fuzzy logic controller is based on two inputs namely sprung mass velocity and unsprung mass velocity. Using a quarter car model with 2 degree-of-freedom the system is modeled and simulated in MATLAB &Simulink® and the results are compared to the widely used sky-hook strategy. the simulation showed the ability of the self-organizing fuzzy controller to provide good results in minimizing sprung mass acceleration in variousroad profiles compared to sky-hookstrategy.